(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper presents an energy-efficient smart automation system based on a hybrid sensing approach using Passive Infrared (PIR) and ultrasonic sensors integrated with Internet of Things (IOT) technology. The main objective of the system is to reduce unnecessary energy consumption by automatically controlling electrical appliances based on human presence. The PIR sensor is used to detect motion, while the ultrasonic sensor measures distance to identify both moving and stationary occupants. A predefined threshold distance of 150 cm and a delay time of 45 seconds are implemented to ensure reliable operation and to avoid unnecessary switching. The sensed data is processed using the ESP 32 microcontroller, which controls the appliances through a relay module. The system supports both local and remote control. A web-based interface developed using XAMPP enables users to monitor and control appliances within a local network, while Blynk Cloud allows remote access through a mobile application. In addition, voice control functionality is provided through the application interface for user convenience. Experimental results confirm that the proposed system effectively reduces energy consumption and achieves significant energy and cost savings under practical operating conditions. The system is simple, cost-effective, and suitable for applications such as smart classrooms, homes, and offices